Phospha-Michael Addition to In Situ Prepared 5-Arylmethylidene Meldrum’s Acids - Adib, Mehdi; Sheikhi, Ehsan; Rezaei, Narjes; Bijanzadeh, Hamid Reza; Mirzaei, Peiman (Synlett, 2014)
Knoevenagel condensation reaction of an aldehyde and Meldrum’s acid produces a 5-arylmethylidene Meldrum’s acid, which undergoes Michael addition of a trialkyl phosphite under solvent-free conditions to afford the title compounds in good yields.
Keywords: trialkyl phosphites; aldehydes; Meldrum’s acid; 2-[(dialkoxyphosphoryl)arylmethyl]malonates; phospha-Michael addition